Constructivism and Arabic Verbal Expression: Linguistic Dimensions of Oral Communication - Sumiati Sumiati; Suliman H Suliman El Warfali; Zeid B. Smeer (Dzil Majaz: Journal of Arabic Literature, 2026)
This study addresses the persistent challenge of low student motivation and limited oral communication competence in Arabic language learning, particularly in maharatul kalam. It aims to examine how a constructivist approach strengthens students’ Arabic verbal expression through meaningful learning experiences and active participation. Using a qualitative case study design, the research was conducted at Kelompok Studi Khusus (KSK) Nurul Jadid. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using thematic analysis. The findings reveal that constructivist learning, implemented through authentic speaking tasks, learner autonomy in selecting themes and presentation styles, collaborative interaction, structured performance activities, constructive feedback, and reward systems, substantially enhances students’ intrinsic and extrinsic motivation. These strategies also foster greater confidence, communicative courage, active participation, and richer linguistic performance in oral Arabic communication. The study contributes to Arabic language pedagogy by demonstrating that constructivist principles effectively integrate cognitive, social, and linguistic dimensions of verbal expression, providing an innovative framework for developing communicative competence and sustainable learner motivation in Arabic speaking instruction